Dihydrotestosterone induces pro-angiogenic factors and assists homing of MSC into the cardiac tissue. (January 2018) - Popa, Mirel-Adrian; Mihai, Maria-Cristina; Constantin, Alina; Şuică, Viorel; Ţucureanu, Cătălin; Costache, Raluca; Antohe, Felicia; Dubey, Raghvendra K; Simionescu, Maya
Abstract : The use of mesenchymal stem cells (MSC) as a therapeutic tool in cardiovascular diseases is promising. Since androgens exert some beneficial actions on the cardiovascular system, we tested our hypothesis that this hormone could promote MSC-mediated repair processes, also. Cultured MSCs isolated from Wharton's jelly were exposed to 30 nM dihydrotestosterone (DHT) for 1 or 4 days and the effects of the hormone on their growth/migration/adhesion and the underlying mechanisms were assessed. Results were obtained by real-time cell impedance measurements, and DNA quantification showed that DHT increased MSC proliferation by 30%. As determined by xCELLigence system, DHT augmented ( 2 folds) the migration of MSC toward cardiac tissue slices (at 12 h), and this effect was blocked by flutamide, an androgen receptor (AR) antagonist. Exposure of cells to DHT, upregulated the gene and protein expression of AR, EMMPRIN and MMP-9 and downregulated the expression of MMP-2 . DHT significantly induced the release of nitric oxide by MSC (≥2-fold) and flutamide blocked this effect. When MSCs were co-cultured with cardiac slices, immunohistochemical analysis and qRT-PCR showed that the integration of DHT-stimulated MSC was significantly higher than that of in controls. In conclusion, our findings provide the first evidence that DHT promotes MSC growth, migration and integration into the cardiac slices. The modulating effects of DHT were associated with upregulation of ARs and of key molecules known to promote tissue remodeling and angiogenesis. Our findings suggest that priming of MSC with DHT may potentially increase their capability to regenerate cardiac tissue; in vivo studies are needed to confirm our in vitro findings.